2018
DOI: 10.1177/2156759x18800285
|View full text |Cite
|
Sign up to set email alerts
|

Remixing the School Counselor’s Tool Kit

Abstract: This article explores a model for school counselors to capitalize on the therapeutic, empowerment-oriented nature of hip-hop practices to engage in youth participatory action research (YPAR). Drawing from research that supports the use of hip-hop therapy and YPAR in schools, we propose a culturally sensitive group counseling process wherein students use hip-hop lyric writing, recording, and performing to critically analyze, research, and report on issues of personal importance to them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 67 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…Six of the articles explored in this study posited that YPAR is an effective medium for aiding students' social/emotional development. Specifically, school counselors can apply YPAR to address race-related stressors inside and outside of school stressors (Edirmanasinghe et al, 2022;Williams et al, 2020) and poverty-related stressors (Smith et al, 2018); to promote emotional processing, well-being, and connectedness (Levy et al, 2018;Smith et al, 2010Smith et al, , 2012; and to decrease anxiety, stress, and/or depression symptoms (Levy & Travis, 2020). According to studies considering youth's college and career development (n = 4), school counselors can use YPAR to grow college-ready research skills and critical consciousness (Scott et al, 2015), career self-efficacy (Edirmanasinghe & Blaginin, 2019), and leadership skills (Ozer & Wright, 2012), and to explore issues of college access (Cook et al, 2019).…”
Section: Outcomes/objectivesmentioning
confidence: 99%
“…Six of the articles explored in this study posited that YPAR is an effective medium for aiding students' social/emotional development. Specifically, school counselors can apply YPAR to address race-related stressors inside and outside of school stressors (Edirmanasinghe et al, 2022;Williams et al, 2020) and poverty-related stressors (Smith et al, 2018); to promote emotional processing, well-being, and connectedness (Levy et al, 2018;Smith et al, 2010Smith et al, , 2012; and to decrease anxiety, stress, and/or depression symptoms (Levy & Travis, 2020). According to studies considering youth's college and career development (n = 4), school counselors can use YPAR to grow college-ready research skills and critical consciousness (Scott et al, 2015), career self-efficacy (Edirmanasinghe & Blaginin, 2019), and leadership skills (Ozer & Wright, 2012), and to explore issues of college access (Cook et al, 2019).…”
Section: Outcomes/objectivesmentioning
confidence: 99%
“…In HHSWT, school counselors allow the acts of writing, recording, and performing emotionally themed hip-hop songs to guide the counseling process. Levy, Cook, and Emdin (2018) discussed the cultural importance of albums or mixtapes in hiphop culture, highlighting that they have traditionally offered marginalized individuals and communities a platform to share complex, untold stories. Mixtape creation is humanistic in nature, given that all songs on the project are chosen solely by the creators and are based on what they deem most important.…”
Section: Mixtapesmentioning
confidence: 99%
“…He also set aside time and space for cogenerative dialogues (Emdin, 2016), in which the students and facilitator worked together to troubleshoot any issues in the class. Students were supported in using their reality and life context in the classroom (Emdin, 2016) to accomplish the course goal of creating a mixtape covering emotional themes deemed relevant to their lives (Levy, Cook, & Emdin, 2018). Further, the course curriculum required that the school counselor/facilitator utilize the HHSWT practices of lyric writing as cognitive journaling, collaboration as role play, and the hip-hop cypher to support students in discussing, writing, and recording emotionally laden songs.…”
Section: The Intervention: Hhswt Coursementioning
confidence: 99%
“…Another creative outlet for research dissemination uses photovoice, where participants use photography to document and express their perspectives of the research project (Royce et al, 2006;Wang & Burris, 1997). Other forms of dissemination include planning a community event, communicating findings and implications online, displaying participant artwork depicting relevant finding, and performing music lyrics disseminated through online medias (Berg et al, 2009;Jennings et al, 2006;Levy et al, 2019;Ozer, 2017;Wilson et al, 2008).…”
Section: Youth Participatory Action Research Definedmentioning
confidence: 99%
“…With these similarities in mind, Levy et al (2019) suggested that pairing HHT with YPAR principles may help counselors to facilitate dialogue about systemic issues that students face through emotional lyric production and group collaboration. The process of lyrical creation, production, and dissemination provides counselors and students the opportunity to engage in discussion about and address salient community issues and thus lends itself well to the YPAR paradigm (Levy et al, 2019). Levy et al concluded that the combining of practices from the fields of HHT, YPAR, and school counseling offer students the opportunity to engage in relevant action research through group collaboration.…”
Section: Ypar and Hip-hop Therapymentioning
confidence: 99%